Manajemen Proyek Informatika - Nurul Hanifah Hasibuan; Zahra Nurhaliza (CV. Multi Kreasi Media, 2024)
Management is the process of organizing, managing, managing human resources, and controlling it in order to achieve the objectives of an activity. Management is indispensable for both personal and business needs. In general, project management is the activity of organizing the information needed in making a project. The goal of project management itself is for the project to run smoothly. Project management can also be a framework that assists project managers in executing, monitoring and controlling projects.